ORGANIZATIONAL STRATEGY OF CORPORATION’S INTERNAL DEVELOPMENT - V. P. Kuznetsov (Russian Journal of Economics and Law)
Objective: to review specific approaches to solving the problems of increasing the efficiency of industrial enterprises production. Methods: situational and economic-statistical analysis. Results: the method of production optimization is proposed. The plan of measures is designed on production improvement, carried out by a specially created working group. The economic effect of the proposed measures is calculated. Scientific novelty: the recommendations made by the author on the restructuring of the corporate management allow to reveal new phenomena and methods of management in the production system. Practical value: the proposals on management improvement were partially implemented in the work of the "Group of companies "GAS" Corporation. The developed recommendations were also used to design the project of "Liteyniy zavod" LLC on the basis of foundry production and the nonferrous foundry workshop.